Effect of water on odorants signals in orange juice by head space-gas chromatography: A possible influence on odor intensity. (July 2021) - Reznik, David; Kaplan, Aviv; Gozlan, Igal; Ronen-Eliraz, Gefen; Avisar, Dror
Abstract: Compounds such as terpenes, alcohols and aldehydes, are key odorants in orange juice. One of the common methods to evaluate the concentration of odorants is headspace-gas chromatography (HS-GC). The concentration of odorants found in the gas phase indicates on their concentration in the liquid, and together with their odor thresholds, can be directly related to odor sensation. However, the addition of water to samples of orange juice concentrate (OJC) that reduces the absolute odorants concentrations in the liquid, seems to significantly increase the signal response of terpenes and long-chain aldehydes measured in the gas phase. This study indicates the effect of water content in OJC on the detection and the intensity of odorants in the gas phase. Therefore, these results demonstrate that water has a significant role in the transition of odor to the gas phase above the liquid matrix. Highlights: Water addition to OJC increase the signal of terpenes in the gas phase. Water content in OJC influence on the detection of odorants in the gas phase. Water has a significant role in the transition of odor to gas phase.